CRITICAL THINKING IN THE FRAMEWORK OF EXPLAINING THE EDUCATIONAL REALITIES OF COLOMBIA - Norberto López (LÍNEA IMAGINARIA, 2025)
Critical thinking, within the framework of explaining the educational realities of Colombia, is fundamental to understanding and transforming the challenges facing the country's education system. Colombian education is characterized by its cultural, social, and economic diversity, which requires a deep and thoughtful analysis to identify the structural causes of its problems. In a broader sense, this article aims to analyze how critical thinking develops within the framework of trying to explain the educational realities of Colombia. To achieve this goal, a qualitative approach will be used, with an interpretive paradigm and a hermeneutic structure, as this is an essay-style text. As a result, it is clear that gaps in access to education, poor infrastructure in rural areas, and the lack of adequate resources limit opportunities for many students. Critical thinking helps analyze these inequalities not only from a superficial perspective, but also by considering their historical, economic, and political roots. This makes it possible to propose contextualized and sustainable solutions that address the root causes of educational gaps in different regions of the country.